MENINGKATKAN MOTORIK HALUS MELALUI COOKING CLASS PADA ANAK USIA 5-6 TAHUN - Siti Aminah, Eneng Sri Susilawati, Suci Aprilyati Ruiyat (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
This study aims to determine fine motor skills through cooking classes in children aged 5-6 years at PAUD Sejahtera Pamarayan district in the Teaching Year 2023-2024, conducted from January to June 2024.The subjects of this study were 5-6-year-olds in group B with a total of 15 children consisting of 5 boys and 10 girls. This research method uses Class Action Research (PTK) which refers to the Kemmis and Mc Taggart Model that uses the four components of action surveillance, namely planning, action, observation and reflection. Based on the results of the development then fine motor skills of children in group B in PAUD Welfare of 15 people, at the time of the pre-study the average ability of children of 44,3% after being given action on cycle I there was an increase with an average of 52,3% based on the data, this study is said to meet the criteria of success, then the study carried out cycle action II. The results of cycle II data obtained data improvement of fine motor abilities in children aged 5-6 years increased by the average of 75,5% then there is an increase from cycle 1 to cycle 2 by 31.3%.